Influence of Job Insecurity and Job Stress toward Employee Turnover Intention Perfomance at PT Samudera Perdana Selaras Semarang - Nabila - Fedorani; Sugiyanta - Sugiyanta; Inayah - Inayah (JOBS (Jurnal Of Business Studies), 2022)
This study aims to analyze the effect of Job Insecurity and Job Stress on Employee Turnover Intention at PT Samudera Perdana Selaras Semarang. This study uses quantitative approach, samples that used in this study is 30 employees of the EMKL division of PT Samudera Perdana Selaras Semarang. Data collection methods that used in this study are questionnaires, interviews and literature study. The questionnaire scale uses a semantic difference scale with a 10-point scale. The data analysis technique that used is multiple linear regression analysis equipped with classical assumption test, t test, f test and coefficient of determination with SPSS 25 software. The results of multiple linear regression show that 1) Job Insecurity (X1) has no partial effect on Turnover Intention (Y), 2) Job Stress (X2) has partial positive and significant effect on Turnover Intention (Y), 3) Job Insecurity (X1) and Job Stress (X2) together have a positive and significant effect on Turnover Intention (Y). The coefficient of determination shows that the variables Job Insecurity and Job Stress contribute 74% to turnover intention while the remaining 26% are influenced by other variables not examined in this study